Analysis of Carrying Capacity of the Bored Pile Foundation in Cibubur Transpark Project - Sanjaya, Arif; Aseanto, Resi (NAROTAMA UNIVERSITY, Indonesia, 2020)
The foundation is a construction that continues the burden of the upper structure and passes it on to the soil below it. A bored pile foundation is now an option in working on structures in densely populated areas and tall buildings. The purpose of this study is to calculate and compare the carrying capacity of the bored pile foundation based on N-SPT data with the O 'Neil & Reese, and Reese & Wright methods, while the Loading test data with the interpretation of the Davisson method and the Mazurkiewicz method. The results of calculations based on N-SPT data, the average ultimate carrying capacity of the foundation with the O’neil & Reese method of 1211.61 tons, Reese & Wright of 1235.02 tons. While the Interpretation of Loading test method for Marzukiewicz is 1267.00 tons, Davisson is 850.40 tons, and the carrying capacity of PDA test results is 121.72 tons. From the calculation of the bearing capacity of the consecutive foundation of the smallest is the Davisson method, the O'neil & Reese method, the PDA test method, the Reese & Wright method, and finally the Mazurkiewicz method.